Foam Roller Post-High-Intensity Training for CrossFit Athletes: Does It Really Help with Recovery? - Fernando Zarzosa-Alonso; Alejandra Alonso-Calvete; Martín Otero-Agra; María Fernández-Méndez; Felipe Fernández-Méndez; Francisco Martín-Rodríguez; Roberto Barcala-Furelos; Myriam Santos-Folgar (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Foam rolling is a new and emergent recovery tool in sports. The aim of this study seeks to compare the acute effects of foam rolling and passive rest on recovery markers in CrossFit athletes following a high-intensity workout. Methods: A quasi-experimental crossover study design was completed with 14 amateur CrossFit athletes. Participants completed the FRAN CrossFit WOD and then completed a recovery protocol including either a foam roller or passive rest. Heart rate, blood lactate, and perceived exertion were collected at three time points (pre-workout, post-WOD, and post-recovery). Results: The foam rolling group had no significant differences from the passive rest group on recovery markers. Blood lactate increased significantly post-WOD in both groups, yet there was no significant difference in blood lactate post-recovery. Perceived exertion and heart rate had a similar pattern to blood lactate. Conclusions: High-intensity training causes significant physiological changes; however, foam rolling offers no additional benefit over passive rest for lactate clearance, heart rate recovery, and perceived exertion. CrossFit athletes can choose their preferred method of recovery based on personal preference, as foam rolling neither enhances nor hinders recovery.